EFFECT OF FEEDING FREQUENCY ON FOOD INTAKE AND CONVERSION IN MYSTUS VITTATUS - Sampath, K; Lakshmanan, G (Indian Journal of Fisheries, 2011)
The amount of food consumed by Mystits vittatus per meal was maximum(54.4 mg dry food per meal) in the lowest feeding frequency (J Ff) and decreasedto the minimum (41.2 mg dry food per meal) in the highest (3/1 Ff). Withincreasing feeding frequency, rates of feeding, absorption and conversion werealso increased. Absorption efficiency, however, remained constant around 90.1%.Contrary to the trend obtained for conversion rate, efficiency of conversion graduallydecreased as the feeding frequency was increased. Net conversion efficiency(18.8%) was maximum in the lowest feeding frequency group (1/2 Ff).Mystus vittatus thus can compensate low feeding schedules by increasing the mealsize and elevating the conversion efficiency.